It's Not All Fiscal : Effects of Income, Fiscal Policy, and Wealth on Private Consumption - Jaramillo, Laura (IMF Working Papers; Working Paper ;, 2015)
We attempt to disentangle income and wealth effects on consumption by disaggregating both the different types of income and wealth. We estimate a consumption function for a panel of quarterly data for 14 advanced economies spanning 1998 to 2012, using an error correction specification. We find a significant long-term relation between consumption and the different components of income and wealth. While fiscal policy had direct effects on consumption, the analysis suggests that wealth effects were sizeable, and therefore need to be kept in mind when analyzing consumption trends going forward.